Efektivitas Cacing Tanah Pheretima hupiensis, Edrellus sp. dan Lumbricus sp. dalam Proses Dekomposisi Bahan Organik - Ea Kosman Anwar (JOURNAL OF TROPICAL SOILS, 2009)
Effectivity of the Earthworms Pheretima  hupiensis, Eudrellus sp. and Lumbricus sp. on the Organic Matter  Decomposition Process (E.K. Anwar): The earthworms  are the one of soil fauna  component in  soil ecosystem have an important role in organic matter decomposition procces. The earthworm feed  plant leaf  and plant matter up to apart and dissolved.  Earthworm  metabolisms  produce like faeces that mixed with decomposed organic matter  mean vermicompost. The vermicompost fertility varies because of some kind of earthworm differ in “niche”  and attitude. The experiment was to study the effectivity of earthworm  on organic matter decomposition which has been conducted in Soil Biological and Healthy Laboratory and Green House of Soil Research Institute Bogor, during 2006 Budget Year. The three kind of earthworms i.e  Pheretima hupiensis, Lumbricus sp. and Eudrellus sp. combined with three kind of organic matter sources i.e rice straw, trash and  palm oil plant waste (compost heap). The result shows that the Lumbricus sp.  are the most effective decomposer compared to Pheretima hupiensis and Eudrellus sp. and the organic matter decomposed by  Lumbricus sp. as followed:  market waste was decomposed of 100%, palm oil empty fruit bunch (compost heap) 95.8 % and rice straw 84.9%,  respectively. Earthworm effectively decreased Fe, Al, Mn, Cu dan Zn.